Developing Competencies for Effective Transfer of Technical Skills - Godihal, Jagdeesh (Journal of Engineering Education Transformations, 2007)
The term "competency" refers to the ability to apply skills and knowledge. In this way it helps to avoid the implication that knowledge or understanding are measured directly, and reinforce the idea that only the results of application of a suite of skills are assessed. In this paper attempt has been made how the competencies of a teacher help in effective transfer of knowledge to the learners.